The Falsification Principle as a Method of Knowledge Growth - Ishaya, Samuel Otu (NIU Journal of Humanities; Vol 9 No 4 (2024): NIU Journal of Humanities, Vol. 9 No. 4, December 2024, 2024)
Karl Popper was not a member of the logical positivist, but he had contacts with them in Vienna in the 1920s. He was critical of their scientific philosophy and condemned their outright rejection of metaphysics as meaningless. His sustained criticism of the logical positivists’ verification principles played a pivotal role in the birth of philosophy of science as a second-order studies in philosophy. His philosophy of science pursued two main concerns – the criteria for the demarcation of science from pseudo-science and a prescription for the methodology of knowledge growth. Although he shared similar concerns with the positivists on the methods of the sciences, they never agreed on a particular method; while the positivists were persuaded that verificationism was the best method for the sciences, Karl Popper was of the opinion that falsificationism was better. For him, falsificationism as a method would not only serve as a method for the sciences but would create room for the growth scientific growth of knowledge generally. The objective of this paper was to evaluate Popper’s notion of falsificationism and its implications for the growth of knowledge and the discovery of truth, not only in the sciences, but in all facets of human endeavour. The analytic method was used for the research. The paper agrees with Popper that the application of the falsification principle will eliminate unverifiable postulations and unfounded doctrines/traditions that tend to encourage ignorance and obfuscate the growth of scientific knowledge. The paper recommends subjecting key legislative, political, religious and scientific assumptions/doctrines to falsification to determine their verisimilitude to truth. Keywords: Falsificationism, Logical Positivism, Dogmatism, Verisimilitude, Logical curiosity.